Patients’ Experience with Received Healthcare in Internal Medicine and Surgery Wards of Slovenian Hospitals—A Cross-Sectional Survey - SKELA-SAVIČ Brigita; BAHUN Mateja; KALENDER SMAJLOVIĆ Sedina; PIVAČ Sanela (Slovenian Journal of Public Health)
The aim of the study was to explore the experiences of patients with delivered healthcare in selected Slovenian hospitals.